Early development of metalinguistic awareness in Japanese: Evidence from pragmatic and phonological aspects of language. Issue 3 (June 2014) - Tsuji, Hiromi; Doherty, Martin J.
The development of metalinguistic awareness for linguistic politeness was examined in 68 Japanese-speaking children aged between three and five years old. A politeness judgement task was administered together with several phonological judgement tasks and false-belief tasks. Four- and five-year old Japanese children, but not three-year-olds, made correct judgements for polite and impolite linguistic expressions by matching the expressions to appropriate social attitudes on the part of the protagonists. Developmental transitions across the age groups were similar for politeness and phonological judgements, with the exception of onset detection. Politeness and phonological judgement performances correlated with each other and were independent of the children's age and receptive vocabulary. However, neither of the aspects correlated with false-belief understanding once age and vocabulary were accounted for. The findings suggest that pragmatic awareness of politeness register develops as early as four years old, in synchrony with phonological aspects at the syllable level.